2006
DOI: 10.1155/2006/149863
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Poor Asthma Control in Children Aged Five to 13 years

Abstract: Despite the high use of inhaled corticosteroids, the majority of children had poorly controlled asthma. The poor control group had more exposure to tobacco smoke and a worse psychosocial impact due to asthma. Few children had past asthma education and action plans, suggesting that there is a need to improve access to and tools for education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 46 publications
1
32
1
1
Order By: Relevance
“…Each hour of smoke exposure per week increased the risk of poorly controlled asthma by 33%. (20) In the present study, we found that a high proportion of children were from households in which people smoked-39 (46.4%) before the educational intervention and 37 (44.0%) after the intervention-although there was no significant difference between the pre-and post-implementation time points in terms of this variable. We believe that one of the reasons for this is that measurements were taken a short time after the CHA-led educational intervention.…”
Section: Discussioncontrasting
confidence: 47%
“…Each hour of smoke exposure per week increased the risk of poorly controlled asthma by 33%. (20) In the present study, we found that a high proportion of children were from households in which people smoked-39 (46.4%) before the educational intervention and 37 (44.0%) after the intervention-although there was no significant difference between the pre-and post-implementation time points in terms of this variable. We believe that one of the reasons for this is that measurements were taken a short time after the CHA-led educational intervention.…”
Section: Discussioncontrasting
confidence: 47%
“…We showed a trend toward more healthcare visits and medication use in children with NCA. Previous studies had already shown the association between healthcare visits and/or medication with uncontrolled asthma . Children with NCA used more antihistamines and cough medication than those with WCA; this association of NCA with a higher use of over‐the‐counter medication was already observed in asthma patients , and it may point to a worst asthma care plan in children with NCA.…”
Section: Discussionmentioning
confidence: 82%
“…Factors associated with poor asthma control include exposure to environmental tobacco smoke and poor parental perception of the psychosocial aspects of asthma (261). A number of tools that allow parents and children to record and describe symptoms have been shown to be helpful:…”
Section: Monitoringmentioning
confidence: 99%